Novel integrated approach modeling proanthocyanidins and bacteriophages to combat multidrug Salmonella Typhimurium in challenged broilers - Al-Khalaifah, Hanan S.; Ibrahim, Doaa; Abdelfattah-Hassan, Ahmed; Ibrahim, Dina; Mohamed Saad, Alaaeldin; Saad, Mai. F.; El-Badry, Sara M.; Elbhnsawy, Reham A.; Azouz, Asmaa A.; Mahmoud, Mayada; Abdel-Raheem, Sherief M.; Ismail, Hesham; et al. (Frontiers in Veterinary Science, 2025)
The emergence of multidrug bacterial isolates, including Salmonella (S.) Typhimurium, which primarily spreads to humans through chicken products, is correlated with a rising prevalence of antimicrobial therapy failure. Thus, we performed a comprehensive analysis of the combined impact of Salmonella bacteriophage (BP) and grape seed oligomeric pro-anthocyanidins (GSOPs) on growth performance, immune functions, antioxidant capacity, cecal microbiota, gut integrity, and S. Typhimurium resistance in challenged broilers. A total of 250 Ross-308 male broiler chicks were offered either a control diet or a diet supplemented with Salmonella BP alone at concentrations of 109 PFU/0.1 ml, GSOPs alone at a level of 400 mg/kg diet, and a combination of both Salmonella BP and GSOPs, and experimentally infected with multidrug-resistant (MDR) S. Typhimurium strain at 14 days of age. Broilers administered BP, GSOPs, and their combination, particularly BP+GSOPs, had enhanced growth performance attributes even following a challenge with S. Typhimurium, alongside decreased mortality percentage, which was evidenced by increased expression of MUC-2, β-defensin-1, cathelicidins-2, JAM-2, occludin, and CLDN-1 genes, reduced S. Typhimurium abundance, and downregulating its virulence-associated genes (sopE and spvC), alongside restored intestinal histological features. GSOPs+BP fortified group exhibited higher cecal beneficial bacteria counts (Bacteroides, Firmicutes, Lactobacillus, and Bifidobacterium species), lower cecal harmful bacteria loads (Escherichia, Enterobacteriaceae, and Clostridium clusters I and IV), decreased serum oxidative markers [H2O2, reactive oxygen species (ROS), and malondialdehyde (MDA)], and increased serum antioxidant enzymes [superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px)]. The incorporation of dietary BP, and GSOPs combination significantly downregulated the intestinal inflammatory regulated genes (IL-1β, IL-6, CCL4, CCL20, COX-2, and iNOS), and mTOR gene, and reduced the serum concentrations of LYZ, NO, CRP, and complement C3, alongside increased serum IgG, and IgM levels, and upregulation of autophagy-related genes (atg5, atg7, atg12, BCLN-1, and LC3-II). The aforementioned beneficial effects of the BP and GSOPs combination support their prospective use in avian nutrition to enhance performance and stimulate immune defense against gastrointestinal illnesses, including S. Typhimurium infection.